Your best just got better : work smarter, think bigger, make more - Womack, Jason W., 1972- (Hoboken, N.J. : Wiley, 2012)
'Imagine if your best just got better every single dayIn Your Best Just Got Better, productivity expert Jason Womack teaches readers that working longer hours doesn't make up for a flawed approach to productivity and performance. Workers need to clarify their habits, build mindset-based strategies, and be proactive. Womack's signature'workplace performance' techniques offer specific strategies to consistently and incrementally improve performance.Readers will: Understand the fundamentals of workflow and the principles of human performance Arm themselves with the tools and the processes to get more of their work done, on time, with fewer resources, and with less stress Making your best better won't happen overnight, but learning how to effectively manage just a few critical success factors lead to an effective workday and an overall successful professional career'--
Includes index.
Keywords: Success in business; Success; Change (Psychology).